Management organization of the LPBA Al Qodiri Jember course program - Maghfirah, Nurriyah; Anam, Syamsul; Maskud, Maskud; Hasan, Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research discusses about: 1) organizing management in Arabic center Al Qodiri Jember, 2) problems in organizing management at Arabic Al Qodiri Jember. This is a descriptive qualitative research. The data are collected by interviews and documentation. Then the data were analyzed in three steps, 1) data reduction, 2) data presentation, 3) drawing conclusions / verification. The results of this research shows that the organizing management Arabic language center Al Qodiri Jember arranged the division of duties and authority of members of the organization based on structure namely linear organization. Authority is not given to just anyone but through a strict qualification system